Implementing SIMANTAP for Personnel Administration Services in Samboja District: An Edward III Policy Implementation Analysis - Hasrullah Hasrullah; Cathas Teguh Prakoso; Santi Rande (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Digital transformation in public administration is a strategic effort to achieve governance that is effective, efficient, and accountable. This study examines the implementation of the Rapid Introductory Letter Administration Service System (SIMANTAP) in Samboja District as a digital innovation in personnel services, aiming to identify factors that hinder its optimal operation. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation. Informants included the Head of Samboja District, the Head of the General and Personnel Subdivision, and SIMANTAP operators at district and village levels. Data were analyzed through data reduction, presentation, and conclusion drawing, using Edward III’s policy implementation model, encompassing communication, resources, disposition, and bureaucratic structure. The findings indicate that initial socialization of SIMANTAP reached 85% of target personnel but lacked ongoing communication. While 90% of staff demonstrated readiness and positive commitment, only 60% had stable access to functional computers and reliable internet. No dedicated budget exists in the regional budget (APBD), and structured monitoring mechanisms are absent. The study concludes that SIMANTAP has strong potential as a district-level e-government model, but its adoption is constrained by limited technological infrastructure, inadequate budgetary support, and a lack of systematic evaluation. Strengthening policy guidance, enhancing staff capacity, modernizing ICT infrastructure, and allocating budgets are critical to ensuring sustainable and effective implementation.